Amazon forest dynamics under changing abiotic conditions in the early Miocene (Colombian Amazonia). (15th June 2016) - Salamanca Villegas, Sonia; van Soelen, Els E.; Teunissen van Manen, Milan L.; Flantua, Suzette G. A.; Santos, Roberto Ventura; Roddaz, Martin; Dantas, Elton Luiz; van Loon, Emiel; Sinninghe Damsté, Jaap S.; Kim, Jung‐Hyun; Hoorn, Carina
Abstract: Aim: We analysed in detail a past marine incursion event in north‐western Amazonia and measured its effect on the forest composition. We also determined the sediment provenance in the fluvio‐estuarine system and reconstructed the overall floral composition of the Amazon lowland forest during the Miocene climatic optimum. Location: A 60‐m‐thick sedimentary succession situated along the Caquetá River in Colombian Amazonia (0.77° S; 71.97° W). Methods: Palynological, geochemical and statistical analyses were performed on samples from organic‐rich sediments. Results: The lower section was formed by fluvial floodplain deposits of Andean provenance rich in pollen of Malvacipolloides maristellae (aff. Abutilon ) and Rhoipites guianensis (aff. Vasivaea ). The middle section was formed by fluvial channel and estuarine swamp deposits of central Venezuelan provenance dominated by pollen of Mauritiidites franciscoi (Mauritia) . Towards the top, the swamp deposits represent an estuarine floodplain with aquatic biomarkers, marine palynomorphs and mangrove pollen. The succession ended with fluvial floodplain deposits of central to southern Venezuelan origin with R. guianensis as dominant pollen type. Palynological diversity was high throughout the section with Andean‐ and Venezuelan‐derived sediments each with their characteristic taxa. Tropical rain forest taxa, such as Arecaceae, Fabaceae, Sapotaceae, Malpighiaceae and Bombacoideae, were common in these sediments, although taxa adapted to drier conditions also occurred. We provide a 'figshare' link to an image library of selected taxa, as well as the raw counts and processed data. Main conclusions: The fluvio‐estuarine system was of mixed origin with sediments and palynomorphs from the emerging Andes, but also from an area situated in the modern Orinoco Basin. Marine influence was linked to the Venezuelan source area and thus of indisputable Caribbean origin. Overall, a mixed forest with drought‐resistant components existed in the drainage system during the Miocene climatic optimum. Our data provide a novel insight into the composition of the tropical lowland forest and the environments in north‐western Amazonia prior to the main uplift of the central and northern Andes.